2007
DOI: 10.1002/bmc.848
|View full text |Cite
|
Sign up to set email alerts
|

Precolumn fluorescence labeling method for simultaneous determination of hydroxyzine and cetirizine in human serum

Abstract: A highly selective and sensitive method was developed for simultaneous determination of the antihistaminic drug hydroxyzine (HZ) and its pharmacologically active metabolite cetirizine (CZ) in human serum using haloperidol as internal standard. The method was based on fluorescence labeling of both drugs with a fluorescent arylboronic acid 4-(4,5-diphenyl-1H-imidazol-2-yl)phenyl boronic acid followed by separation on silica column using a mobile phase consisting of acetonitrile and water (90:10, v/v%) containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The pre-column derivatization HPLC based on the proposed reaction allowed the sensitive detection of aryl bromides with the detection limits of 13-157 fmol/injection. We previously demonstrated that Suzuki coupling reaction was well applied to biomedical analysis [5,[7][8], and therefore the fluorogenic derivatization reaction will become a promising tool for the development of sensitive determination method for aryl halides. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-column derivatization HPLC based on the proposed reaction allowed the sensitive detection of aryl bromides with the detection limits of 13-157 fmol/injection. We previously demonstrated that Suzuki coupling reaction was well applied to biomedical analysis [5,[7][8], and therefore the fluorogenic derivatization reaction will become a promising tool for the development of sensitive determination method for aryl halides. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we found that Suzuki coupling proceeded well without the interference with biological compound and this was the practical reaction for biomedical analysis. By using DPA, we have developed the determination method for aryl halide drugs including clofibrate [5], haloperidol [7] and hydroxyzine [8] Subsequently, we established pre-column derivatization HPLC method for aryl bromides to evaluate the analytical performance of the proposed derivatization reaction. Tesque (Osaka, Japan).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DPA-labeled compounds can be detected clearly without interference on the chromatogram because DPA does not react with most of biological compounds. The practicability of the labeling procedure by DPA was confirmed in the successful analysis of the aryl halide drugs including clofibrate [5], haloperidol [7] and hydroxyzine [8] in biological fluids.…”
Section: Introductionmentioning
confidence: 90%
“…2); 50 mM was selected as optimum concentration. Pd(OAc) 2 was decisively selected as the catalyst due to its success for the labeling reaction in our previous reports [6,9,10]. The concentration of Pd(OAc) 2 was varied from 1 to 5 mM, the optimum RFI was observed over 3 mM; 4 mM was selected.…”
Section: Optimization Of Labeling Conditionsmentioning
confidence: 99%
“…We have since employed Suzuki coupling reaction as a pre-column fluorescent labeling step to develop sensitive and selective methods for drugs analysis using fluorescence detection [9,10].…”
Section: Introductionmentioning
confidence: 99%